Detection of SARS-CoV-2 in Cervical Smears in a Sample of Iraqi Women - Dr. Zainab Bashar Kamal; Dr. Tagreed Hamood Hatem (Academic Journal of Clinicians, 2024)
Background: The COVID-19 outbreak in Iraq is a component of the global pandemic of coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Objective: Search for the presence of SARS-CoV-2 in cervical mucosa of females with already positive throat sample for SARS-CoV-2. Patients and methods: In this observational cross sectional study, one hundred women (Fifty women with confirmed COVID-19 positive infection and other fifty without) attended to the Baghdad Teaching Hospital from April 2020 to June 2021 were included. An analysis was conducted on medical records, laboratory findings, and computerized tomography tests. The assessment of probable genital infection involved the examination of cervical tissue taken from cervical swab samples to detect the presence of SARS-CoV-2. The utilization of reverse transcriptase polymerase chain reaction (RT-PCR) was employed to validate the presence of SARS-CoV-2 infection in cervical tissue. Results: A total of 50 patients with positive COVID-19 throat swab were enrolled in this study (43 patients mild; 7 patients severe) and compared with control group (50 patients with negative COVID-19 throat swab). Mean age of COVID-19 positive group was (36.6 ± 13.777) years, while in COVID-19 negative group was (36.2 ± 12.214) years. Premenopausal women in COVID-19 positive group were 40 patients (80%) while 10 Patients (20%) were postmenopausal. In comparison with control group, 45 patients (90%) were premenopausal and 5 patient (10%) were post-menopausal. Regarding of pregnancy, there were 32 pregnant women in COVID-19 positive group versus 31 women in control group (P value= 0.836). There was non statistically significant difference between COVID-19 positive group and control group regarding their age (P value = 0.878). Moreover, there was nonsignificant difference between COVID-19 positive group and control group according premenopausal and postmenopausal age (P value = 0.262). Of 50 patients with COVID-19 positive throat swab, 6 women had positive cervical swabs, while 44 women were negative. All 50 patients in control group who had throat negative COVID-19 had negative cervical swabs. There was significant difference between COVID-19 positive and control group concerning COVID-19 cervical swabs (P value = 0.027). Conclusion: The finding of SARS-CoV-2 in cervical swap in patients with positive throat swap PCR arise the likelihood of SARS-CoV-2 in cervical mucosa as a part of viremia state may be sexually transmitted and the likely hood of a long term effect of the virus on the cervix at the cellular level.